Cranberry fruit powder (Flowens™) improves lower urinary tract symptoms in men: a double-blind, randomized, placebo-controlled study - Vidlar, Ales; Student, Vladimir; Vostalova, Jitka; Fromentin, Emilie; Roller, Marc; Simanek, Vilím; Student, Vladimir (World journal of urology, 2016)
BACKGROUND: Lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia increase with age. To date, several medications are available to treat LUTS, including herbal remedies which offer less side effects but lack robust efficacy studies. METHODS: This 6-month, randomized, double-blind, placebo-controlled study aimed at evaluating the dose effect of 250 or 500 mg cranberry powder (Flowens™) on LUTS and uroflowmetry in men over the age of 45. A total of 124 volunteers with PSA levels <2.5 ng/mL and an international prostate symptoms score (IPSS) score ≥8 were recruited and randomized. The primary outcome measure was the IPSS, evaluated at 3 and 6 months. Secondary outcome measures included quality of life, bladder volume (Vol), maximum urinary flow rate (Q max), average urinary flow rate (Q ave), ultrasound-estimated post-void residual urine volume (PVR), serum prostate-specific antigen, selenium, interleukin 6, and C-reactive protein at 6 months. RESULTS: After 6 months, subjects in both Flowens™ groups had a lower IPSS (-3.1 and -4.1 in the 250- and 500-mg groups, p = 0.05 and p < 0.001, respectively) versus the placebo group (-1.5), and a dose-response effect was observed. There were significant differences in Q max, Q ave, PVR, and Vol in the Flowens™ 500-mg group versus baseline (p < 0.05). A dose-dependent effect on Vol was observed, as well as on PVR, for participants with a nonzero PVR. There was no effect on clinical chemistry or hematology markers. CONCLUSIONS: Flowens™ showed a clinically relevant, dose-dependent, and significant reduction in LUTS in men over 45.
Keywords: Humans; hyperplazie prostaty; Phytotherapy; lidé středního věku; fytoterapie; Double-Blind Method; následné studie; výsledek terapie; lidé; dvojitá slepá metoda; Lower Urinary Tract Symptoms; močení; Prostatic Hyperplasia; časové faktory; Follow-Up Studies; Male; Middle Aged; Powders; Treatment Outcome; Urination; ovoce; Vaccinium macrocarpon; Fruit; prášky, zásypy, pudry; mužské pohlaví; Time Factors; symptomy dolních močových cest